2007
DOI: 10.1007/s15010-007-6144-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candidemia in a Tertiary Care Centre of North India: 5-Year Study

Abstract: These results were comparable to those derived from other regions of India. C. tropicalis has been reported as the predominant species involved in the cases of candidemia. But in 2005 it has moved toward C. parapsilosis. No true antifungal resistance is reported. Further epidemiological surveillance is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

30
77
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 26 publications
30
77
2
2
Order By: Relevance
“…Furthermore we noted no resistance in C. albicans isolates and a low level of resistance among the C. tropicalis and C. parapsilosis isolates. In a previous study, we reported similar observations, with no resistance seen in strains of these commonly isolated species (Xess et al, 2007). In contrast, we observed a high level of resistance to fluconazole in C. rugosa strains, with 16.0 % (4/25) resistant and 12.0 % (3/25) SDD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore we noted no resistance in C. albicans isolates and a low level of resistance among the C. tropicalis and C. parapsilosis isolates. In a previous study, we reported similar observations, with no resistance seen in strains of these commonly isolated species (Xess et al, 2007). In contrast, we observed a high level of resistance to fluconazole in C. rugosa strains, with 16.0 % (4/25) resistant and 12.0 % (3/25) SDD.…”
Section: Discussionsupporting
confidence: 85%
“…Although C. albicans remains the most commonly isolated species from cases of candidaemia in the USA, Europe and South America (Brazil), its dominance is slowly giving way to an increase in non-albicans species such as Candida glabrata (Colombo et al, 2006;Horn et al, 2009;Pfaller & Diekema, 2007;Tortorano et al, 2004). However, in Asian countries like India, Candida tropicalis appears to be emerging as the most common cause of candidaemia (Chakrabarti et al, 2009;Xess et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the substantial morbidity and mortality associated with these infections it is clear that fungal diseases have emerged as important public health problems (Pfaller & Diekema, 2007). While Candida albicans remains the most common causative agent of candidaemia, the incidence of Candida parapsilosis has increased significantly, outranking C. albicans in some studies, depending on the period and geographical area (Aittakorpi et al, 2012;Lagrou et al, 2007;Lockhart et al, 2012;Maganti et al, 2011;Nucci et al, 2013;Parmeland et al, 2013;Tragiannidis et al, 2012;Wu et al, 2011;Xess et al, 2007). Candidaemia risk factors include the use of broad-spectrum antibiotics, cancer chemotherapy, immunosuppressive agents and indwelling medical devices (Tumbarello et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal sensitivity pattern of Candida that was isolated from blood and colonized site (mouth, rectum) was identical in 64.2% (9/14) neonates, indicating the probable site of entry. Prior colonization of mucous membrane has been reported to be an important risk factor for invasive candidiasis by several authors 17,23 . In a recent study we found that 80% Candida spp.…”
Section: Discussionmentioning
confidence: 99%